Analisis Prosedur Laporan Pajak Pertambahan Nilai (Ppn) di PT Berhasil Indonesia Gemilang - Firdaus, Andika Adam; Nugroho, Rusdi Hidayat (Business and Investment Review, 2025)
This study aims to describe and analyze procedures for reporting value added tax of PT. Berhasil Indonesia Gemilang is in accordance with the taxation law, Law Number 42 of 2009. The research method used is a qualitative descriptive analysis method. The results show that the value added tax reporting procedure at PT. Berhasil Indonesia Gemilang in 2014 and 2015 has not complied with the reporting procedure, namely the reported party is empty (0) and the date of reporting was carried out in 2016. However, in 2016 PT. Berhasil Indonesia Gemilang performs reporting procedures correctly. Due to mistakes in 2014 and 2015 PT. Berhasil Indonesia Gemilang received a tax sanction in the form of an examination. Sanctions obtained by PT. Berhasil Indonesia Gemilang can be forgiven by utilizing the tax amnesty program in the first phase held by the government.